178 COMT Val158Met is Associated With Domain-Specific Cognitive Impairment Following Mild Traumatic Brain Injury. (August 2015) - Yue, John K.; Winkler, Ethan A.; McAllister, Thomas W.; Temkin, Nancy; Ferguson, Adam; Lingsma, Hester F.; Yuh, Esther; Tarapore, Phiroz E.; Sharma, Sourabh; Puccio, Ava; Wang, Kevin; Mukherjee, Pratik; et al.
Abstract : INTRODUCTION: Mild traumatic brain injury (mTBI) results in variable clinical outcomes, which may be influenced by genetic variation. A single-nucleotide polymorphism in catechol-o-methyltransferase (COMT), an enzyme that degrades catecholamine neurotransmitters, may influence cognitive deficits following moderate and/or severe head trauma. However, this has been disputed and its role in mTBI has yet to be studied. METHODS: A retrospective analysis of the Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot (TRACK-TBI Pilot) study was conducted to determine whether the COMT Val158Met polymorphism influences outcome on a cognitive battery 6 months following mTBI Wechsler Adult Intelligence Test Processing Speed Index Composite Score (WAIS-PSI), Trail Making Test (TMT), and California Verbal Learning Test (CVLT). RESULTS: In 93 predominately white subjects, we demonstrate that the COMT Met158 allele associates with improved processing speed (mean increase 10.3 points, 95% CI [3.5-17.1], P = .004) and mental flexibility (mean decrease 21.6 seconds [1.4-41.8], P = .037) on WAIS-PSI and TMT, respectively, compared with Val158/Val158 homozygotes. The association between the COMT Met158 allele and WAIS-PSI persists after controlling for effects of age and years of education (mean increase 8.0 points [1.4-14.7], P = .019). The association between the COMT Met158 allele and TMT completion times demonstrated a statistical trend after controlling for age and education (mean decrease 16.1 seconds [−34.0 to 1.8], P = .078). Older age and decreased education associate with impairment on WAIS-PSI and TMT independent of COMT. COMT Val158Met did not influence verbal learning on CVLT. CONCLUSION: COMT Val158Met may exert domain-specific cognitive protection following mTBI.